BPEL Unleashed putting a modern business process execution standard to work. - Sherman, Doron
BPEL (Business Process Execution Language) makes business processes and composite Web services first class citizens of the Java and .NET platforms, while preventing vendor lock-in. The result is a drastic reduction in the complexity, delivery time and cost associated with implementing workflow, BPM (business process management) and related business integration projects.